Cultivating Character for Indonesia’s Golden Generation: Strengthening Student Values for National Progress - Hernawati Hernawati; Supala Supala; Iim Ibrohim; Dewi Mulyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Indonesia's national development depends on cultivating a "Golden Generation"—youth who combine intellectual prowess with strong moral character. Character education is viewed as essential to shaping ethical, responsible future leaders. This mixed-methods study investigated the role of character education in student development. Data were collected from 422 students across 30 Indonesian universities through surveys, interviews, and focus group discussions. Findings reveal that 78% of students and 85% of educators observed notable improvements in student behavior, including enhanced discipline, empathy, and responsibility. Despite these benefits, challenges persist. Overloaded curricula, limited funding, and a shortage of trained educators were cited as key barriers to effective implementation. Furthermore, students expressed a need for character education programs that are more practical and aligned with real-world scenarios. While character education significantly contributes to personal growth and social behavior, structural issues hinder its full potential. Integrating character education into existing curricula and investing in teacher training are essential steps forward. Character education plays a vital role in shaping the Golden Generation and, by extension, Indonesia’s future leadership. To maximize its impact, educational policies must address systemic barriers and promote accessible, context-relevant character development programs